The Development of Adolescent’s Inner Strength through Integrative Group Counseling Model - Wattanaskulkiat, Sangdao; Nattaporn , Nattaporn; Prayoonsak, Suradate (Journal of Social Sciences Naresuan University, 2025)
This study aims to investigate and evaluate the effectiveness of the integrative group counselling model in developing university students’ inner strength. Twenty undergraduate students from Naresuan University aged 19-25 years old who completed the inner strength questionnaire participated in the study. The students were assigned to either control or experimental groups using the simple random sampling method (10 students in each group). This study was divided into three phases which were pre- and post-experimental phases, and the follow-up phase. The research instruments were 1) an inner strength scale and 2) the integrative group counselling model for loneliness. Data were analyzed using percentage, mean, and standard deviation. The difference in the inner strength between the experimental and control groups was compared using Paired Samples T-test while T–test independent was used to analyze the difference between the before, after and follow-up phases. The study indicated that students in the experimental group had better inner strength scores in the post and follow-up phases than the pre-experimental phases at a .05 statistically significant level, while the inner strength score in the control group showed no statistically significant difference in three phases.